Katie and the carnival: bedtime books - Spurgeon, Maureen (Brown Watson England, 1992)
"Katie and the Carnival" follows a young girl named Katie as she embarks on an exciting adventure at a vibrant carnival. Filled with thrilling rides, colorful games, and delicious treats, Katie experiences the joy and wonder of the festivities. Along the way, she learns about friendship, courage, and making the most of every moment, capturing the magic of a day filled with fun and discovery.